The fallibility of Anne Bradstreet : exploring the valuable imperfection of America’s first great female poet - Ooi, Nicole Wei Lyn (2017)
Through an examination of Anne Bradstreet's poetry, this essay highlights the fallibility present in her poems, that of which points to the authenticity and relatability of her poetry through time and place.